Gdy piasek, kamień i beton stają się sprawcze. Nowy materializm i badanie architektury - Włodarek, Mateusz (Artium Quaestiones, 2025)
The article analyses the agency of matter in the architectural design process, emphasizing that it does not merely serve as a passive background but plays an active role in shaping architectural form. Referring to the principles of new materialism, particularly the works of Jane Bennett and Karen Barad, the author highlights the agentic potential of matter, which influences the course of design processes and modifies the initial design intentions. The analysis of materials such as stone, concrete and sand demonstrates how matter actively participates in the creation of architecture, shaping the final form of structures. The aim of the article is to view buildings as dynamic structures emerging from the complex interaction between humans and materials.